Katsura Funakoshi - Ernst Barlach : A Map of the Time. - Blomberg, Katja; Giesen, Sebastian; Schick, Karin; Annely Juda Fine Art, London; Ernst Barlach Haus - Stiftung Hermann F. Reemstma, Hamburg (London : Annely Juda Fine Art, 2005)
Barlach, Ernst
Katsura Funakoshi Ernst Barlach A Map of the Time, Annely Juda Fine Art, London, 27 January - 24 March 2005 / Ernst Barlach Haus - Stiftung Hermann F. Reemstma, Hamburg, 24 April - 24 July 2005
kunstcatalogus
Keywords: Funakoshi, Katsura; Barlach, Ernst